A lung adenocarcinoma patient with EGFR mutation in exon 18 and ALK-rearrangement who treated with erlotinib and crizotinib - Mehmet Artaç; Levent Korkmaz; Mustafa Karaağaç; Buğra Kaya; Necdet Poyraz; Hakan Özön; Zehra Er; Lema Tavlı (Journal of Oncological Sciences)
Concomitant mutations of echinoderm microtubule-associated protein-like 4 (EML4) anaplastic lymphoma kinase (ALK) translocation and epidermal growth factor receptor (EGFR) can be found rarely in lung adenocarcinoma. We present a case of harboring EML4/ALK rearrangement lung adenocarcinoma who previously received erlotinib. A 42-year-old male who was diagnosed as lung adenocarcinoma and received many series of cytotoxic regimens. A partial tumor response was achieved with crizotinib after failure with erlotinib therapy. After progressive disease, biopsy of new liver lesion showed EML4/ALK rearrangement. Thus crizotinib was administrated. A partial tumor response was achieved with crizotinib after failure with erlotinib therapy and chemotherapy. We conclude that it is important to evaluate for EML4/ALK rearrangement even the patient has EGFR mutation. Concomitant EGFR exon 18 and EML4-ALK mutations can occur in lung adenocarcinoma. EML4/ALK related TKIs may be more effective in these patients. Keywords: Non-small cell lung cancer, Erlotinib, Epidermal growth factor receptor, Anaplastic lymphoma kinase, Crizotinib